EDUKASI PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) DAN UPAYA PENERAPAN KESELAMATAN KESEHATAN KERJA DI PANTI ASUHAN ASUHAN MUHAMMADIYAH YULIWIS RESMAN - Royani Chairiyah; Sari Narulita (Jurnal Abdi Insani, 2023)
One of the strategies to reduce the spread of COVID-19 in orphanages is to socialize Clean and Healthy Behavior (PHBS) and the application of Occupational Safety, Health and Health (K3) through education. The majority of orphanage residents, including caretakers, caregivers, and caretakers, are used to participating in activities together. The possibility of spreading the disease Covid-19 is present in this situation. To prevent transmission of the Corona virus, orphanage managers must be able to anticipate residents coming in and out of the orphanage, as well as outside parties such as food providers and other needs. Purpose: Increase the knowledge, understanding and behavior of managers and the use of OSH during the COVID-19 pandemic among children at the Yuliwis Resman Orphanage. This service activity is carried out by conveying PHBS information and the use of K3 in preventing Covid through audio-visual media, questions and answers, and demonstrations. Pre and post tests were carried out during the activity, which involved 31 children and adolescents as well as 8 supervisors and caregivers. After the activity, participants' knowledge and understanding of the implementation of PHBS and K3 increased. Participants increased the average point score from the pre-test to 67 and the average post-test score to 95 by successfully demonstrating how to wash their hands and answering the questions asked. Orphanage managers, caregivers and residents become more aware of PHBS and the efforts made to implement occupational safety and health by demonstrating one of the clean and healthy living behaviors, namely washing hands properly, how to maintain the cleanliness of the orphanage.